Thermodynamic properties of Ce(RuxRh1-x)3B2 - Berger, S.; Hauser, R.; Michor, H.; Hilscher, G.; Bauer, E.; Sereni, J.G.; Rogl, P.; Sereni, Julián (Elsevier, 1999)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina